Maintenance Strategy for the Muliama-Wa2e-Makki Road Section in Jayawijaya Regency, Papua Province, Highlands - Elias Komba; Bahtiar Bahtiar; Harmonis Rante; Mujiati Mujiati; Dewi Ana Rusim (Publikasi Indonesia, 2024)
In Jayawijaya Regency, there are several prioritized road sections, including national, provincial, and district roads. The Muliama-Wame-Makki road section is classified as a provincial road serving as an alternative route, with a total length of 22 kilometers connecting Jayawijaya Regency and Lanni Jaya Regency. The traffic on this road is quite heavy with a diverse composition (Mixed Traffic). An analysis using the Pavement Condition Index (PCI) was conducted based on field survey data, including measurements of the extent, types, and quantities of surface damage per 200 meters along each road segment. The types of damage observed on the Muliama-Wame-Makki road section include patching, longitudinal cracks, alligator cracking, and pavement subsidence, with a total damage percentage of 1.684%. The maintenance strategy is determined based on the PCI calculation and Bina Marga method, suggesting that routine maintenance is sufficient for addressing the observed issues.